(untitled) (Research, Society and Development, 2021)
In this investigation, the influence of gamma radiation in a therapeutic dose, such as the dose generally administered (on average) in two cycles of radiotherapy treatment, was evaluated for the chemical characteristics of nanocomposite films formed by polycaprolactone (PCL) with oxide nanoparticles of ZnO (ZnO NPs). The PCL nanocomposite films with ZnO NPs (PCL/ZnO NCs) were obtained via solvent casting method, using chloroform as solvent, with ZnO NPs mass contents in relation to polymer masses equal to: 02%; 0.4%; 0.6%; 0.8% and 1.0%. After this step, the films obtained were exposed to gamma radiation in a dose of 140 Gy in the presence of air and at room temperature. The influence of gamma radiation in a therapeutic dose on the chemical characteristics of nanocomposite films obtained through the solvent casting method, was accessed through absorption spectroscopy in the infrared region. Our results indicate that the chemical structure of PCL is preserved after exposure to gamma radiation at 140 Gy.